The Influence of Intellectual Capital on the Market Value: Evidences from Food and Beverage Company in Indonesia - I Gede Adiputra; Nyoman Suprastha; Azhar Affandi (International Journal of Supply Chain Management, 2020)
The present study investigated the relationship between human capital, structural capital, capital employed and market value with the mediating intervention of supply chain management in Indonesia This study uses purposive sampling method with 34 total sample companies and applies the VAIC method in carrying out its measurements. The measurement of market value used in this study is market to book value. The result shows that IC as a whole has significant positive effect on market value. Human capital has significant positive effect on market value. Structural capital does not significantly affect the market value of the company. Capital employed has significant negative effect on the market value.